Faktor Host Yang Berhubungan Dengan Kejadian Tuberculosis Paru Di Puskesmas Kecamatan Setiabudi - Melinda, Vena; Handayani, Rini; Sangadji, Namira Wadjir; Wahidin, Mugi (Universitas Esa Unggul, 2024)
Pulmonary tuberculosis (TB) is an infectious disease that is still a problem in the world. TB can cause death in sufferers. Based on data from patients who came to visit Poli Ratu, the percentage of pulmonary TB in 2019 was 25.8%, totaling 381 cases, in 2020 the percentage of pulmonary TB was 17.5%, this shows that the percentage of pulmonary TB in the community is quite high. The purpose of this study was to determine the factors associated with the incidence of pulmonary TB at the Setiabudi District Health Center in 2021. This study was conducted using a cross sectional design with a quantitative approach. Data collection techniques using secondary data. The population and sample were 97 patients who were recorded in 2021 with a sampling technique using simple random sampling. Data analysis was performed using univariate and bivariate tests using chi-square statistical test with =0.05. The results of this study indicate that there are 32.0% of respondents who have pulmonary TB. Based on the results of the bivariate test, it was found that there was a relationship between age (p-value = 0.035), gender (p-value = 0.004), education (p-value = 0.049), occupation (p-value = 0.016), and nutritional status (p-value = 0.049) with the incidence of pulmonary TB. The incidence of pulmonary TB increased in male respondents of productive age with the last primary-secondary education and active working status, with poor nutritional status at the Setiabudi District Health Center.